MODEL INTEGRASI DESIGN DAN PROSES MANUFAKTUR PADA PERAKITAN PRODUK MULTI-PEMASOK - Budi Susanto, MK Herliansyah, dan Alva Edy Tontowi (Jurnal Teknosains, 2013)
In Product design process, aspects related to the manufacturing process and supply chain should be considered. The design is produced not only satisfy for consumers needs but it fulfilled the constraints related to manufacturingand supply chain aspects. This research aims to make a model to determine the cheapest product design from both of manufacturing process and supply chain. This research uses binary programming as an approach. The cost aspects used in this research are component’s manufacturing cost, supplier fixed contact cost, assembly operation cost and quality improvement cost. The result of research, a physical product design with the lowest total cost by combining components from several designs and adding the value constraint on the quality specification.